Karakteristik Pembakaran Droplet Campuran Bensin Oktan Rendah dengan Penambahan Minyak Kulit Jeruk - Musyaroh; Anisah Nurul Izzah; Rizqa Ruviana; Fatkhurrohman; Tria Puspa Sari; Widya Wijayanti (Universitas Muhammadiyah Metro, 2026)
The use of waste as an alternative fuel is being continually developed to support the clean energy transition. Orange peel oil (OPO) contains limonene, a volatile hydrocarbon compound with double bonds that has the potential to be used as a gasoline additive. However, studies directly examining its effect on droplet combustion characteristics are still limited. This study aims to fill this gap by evaluating the droplet combustion dynamics of a mixture of low-octane gasoline and OPO through visual and thermal approaches. Experiments were conducted by burning 10 µL droplets using a metal stand, with the essential oil concentration varying from 1% to 100%. Visualization was performed using a high-speed camera, and temperature measurements were carried out with a K-type thermocouple. The results showed that the addition of OPO prolonged the combustion time, decreased the combustion rate constant, and increased the maximum temperature. Microexplosions were observed starting at concentrations ≥25%, due to differences in boiling points between the components. Flame visualization confirmed the quantitative results, with brighter and longer-lasting flames at higher concentrations. This study concludes that OPO can significantly modify the droplet combustion characteristics and shows potential as a waste-based biofuel additive, which can improve the efficiency and sustainability of gasoline combustion systems